The The Evolution of Vertical Video: TikTok and the 21st Century Children's Interactive Learning Trend - Sudarmanto, Joni Agung (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2023)
This study tries to discuss how the evolution of vertical video contributes as a learning medium for children in the 21st century. Furthermore, vertical video as learning media refers to the trend of the 21st-century education world, which prioritizes flexibility in learning modes and media. This flexibility also contributes to the increasing massive emergence of contemporary learning media, especially for children, which prioritizes interactivity through the concept of public pedagogy. This study uses a multi-site qualitative. With a literature study of 34 articles covering 21st-century interactive learning from the search databases JSTOR, Taylor Francis, Wiley Library, ScienceDirect, and Google Scholar with keywords: "children's education," "interactive education," and "social media education." Then, a content analysis was conducted to discuss vertical videos as a medium for children's learning on TikTok. The study results show that the evolution of vertical video is good because it is by human ergonomics, which is seen as a vertical creature. Likewise, when he synergizes with TikTok, which gets a good response from children, it becomes a learning medium. On the other hand, TikTok provides opportunities through alternative space and opportunity space for learning media creators and students to collaborate in the scope of digital art, digital creation, and interactive public pedagogy.